Pengaruh Pemahaman Kode Etik terhadap Etika Profesional Dosen di Fakultas Dakwah dan Ilmu Komunikasi Universitas PTIQ Jakarta - Kuswara, Nanang; Muzayyanah, Agustriani; Djunaid, Jamaluddin (IDARI: Jurnal Manajemen Dakwah, 2025)
This study examines the influence of code-of-ethics comprehension on the professional ethics of lecturers at the Faculty of Da’wah and Communication Sciences, Universitas PTIQ Jakarta. The research is grounded in the importance of ethical principles as the foundation of academic conduct, particularly within Islamic higher education institutions that emphasize Qur’anic values in organizational governance. A quantitative survey method was employed, using an online questionnaire distributed to 14 permanent and non-permanent lecturers. Data were analyzed using simple linear regression to measure the relationship between code-of-ethics comprehension (variable X) and lecturers’ professional ethics (variable Y). The findings indicate that lecturers’ comprehension of the code of ethics is generally good, although some respondents are not yet familiar with the formal document in which the code is stipulated. Lecturers’ professional ethics—which include integrity, discipline, responsibility, and the implementation of the Tri Dharma—are categorized as very high. Regression analysis demonstrates that comprehension of the code of ethics has a positive and significant effect on lecturers’ professional ethics, as reflected in strong regression coefficients across teaching, research, and community service dimensions. These results highlight the importance of strengthening code-of-ethics socialization and internalizing Qur’anic ethical values to enhance lecturer professionalism and foster an ethical academic culture within the Faculty of Da’wah at Universitas PTIQ Jakarta.